Reflexes of Old Vowels in Noun Word Change System in Western Polisian and Related Patois (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The system of noun word change is analyzed on the material of Western Polisian and related patois to reveal the phonetic regularities in the patois inflection system  and the specificity of the reflection processes in etymological vowels in particular. It is ascertained that the inflectional variability in the substantival paradigm is mostly determined by the continuants of the old inflection h and also etymological *o and *e whose reflection quality depends, as a rule, on the non-stressed position conditioning the position of the corresponding word forms.
Keywords: patios; vowel phonemes; old vowel reflexes; noun; case; inflection